Characteristics of zoonotic gastrointestinal parasite infections in owned dogs. Lima-Peru (Veterinary Science, 2020)
Urban growth in Peru is accompanied by an increase in dog ownership. Which constitutes a potential risk in the transmission of zoonotic diseases. The objective of the research was to describe the characteristics of the zoonotic gastrointestinal parasite infections in dogswith an owner. For this, 296 stool samples from patients treated in veterinary clinics located in the districts of South Central (Miraflores, Chorrillos) and South (San Juan de Miraflores) Lima were analyzed. Of which 288 were positive for gastrointestinal zoonotic parasites during the period 2015 - 2018. Likewise, the direct examination and the flotation concentration test were carried out to identify zoonotic parasites. Regarding the results, infection caused by Giardia spp (66,3%) was the most frequent, followed by Toxocara canis (18,8%), Ancylostomacaninum (3,5%) and Dypilidium caninum (2,4 %). Likewise, a higher frequency of parasites was observed in the diarrheal feces of male dogs (52,8%) of small breeds (43,8%). Mixed-breed dogs (12,2%), English Bulldog (10%) and Labrador retriever (9,7%) were the most frequently infected. It is concluded that 97,3% of the owned dogs were infected with zoonotic gastrointestinal parasites, which constitutes a problem for public health.
Keywords: Helminths; dogs; intestinal parasites; zoonosis